Dermoscopic features of hidroacanthoma simplex: Usefulness in distinguishing it from Bowen's disease and seborrheic keratosis. Issue 10 (19th May 2015) - Shiiya, Chihiro; Hata, Hiroo; Inamura, Yuka; Imafuku, Keisuke; Kitamura, Shinya; Fujita, Hiromi; Shimizu, Hiroshi
Abstract Hidroacanthoma simplex (HAS) is a rare benign eccrine adnexal tumor. HAS is sometimes clinically or pathologically misdiagnosed as squamous cell carcinoma in situ (Bowen's disease; BD), seborrheic keratosis (SK) or other adnexal tumor. To date, there has never been a report focusing on dermoscopic features to distinguish HAS from BD and SK. We found the following dermoscopic findings to be characteristic of HAS: fine black dots/globules (75% of cases) and fine scales arranged annularly (100% of cases). In contrast, glomerular vessels, which are typically observed in BD, were not seen in any of the four cases. Cerebriform appearance and milia‐like cysts, which are typically observed in SK, were also not seen in any of the four cases. The existence of "scattered fine black dots/globules" and "fine scales arranged annularly", and the absence of the glomerular vessels, may contribute to precise diagnosis of HAS. Even though HAS resembles BD or SK clinically, it can be distinguished from these by the characteristic dermoscopic features.